Growth and Yield of Brazilian Spinach Plant (Alternanthera Sissoo) Under The Treatment of Types and Dosages of Organic Fertilizer - Tasya Tasya Amelia Setiawan; I Gusti Bagus Udayana; Made Sri Yuliartini; Yohanes Parlindungan Situmeang (Agriwar Journal, 2026)
Brazilian spinach is a highly nutritious vegetable, offering a rich profile of essential components, including minerals, vitamins A, B6, and C, antioxidants, and folic acid. Given its significant potential, sustainable cultivation methods are encouraged, particularly through the application of organic fertilizers to meet the plant's nutritional needs. This study aimed to evaluate the impact of various types and dosages of organic fertilizers on the growth and yield performance of Brazilian spinach. The experiment took place at the Wet Laboratory, Faculty of Agriculture, Science, and Technology, Warmadewa University, located on Jalan Terompong No. 24, Denpasar. A factorial Randomized Block Design was employed, examining two factors: organic fertilizer type (J1: rabbit manure, J2: chicken manure, J3: goat manure) and fertilizer dosage (D1: 5 tons/ha, D2: 10 tons/ha, D3: 15 tons/ha, D4: 20 tons/ha). Results indicated that the highest total fresh economic yield per plant was achieved using rabbit manure (115.33 g), representing a 29.58% increase compared to the lowest goat manure treatment (89.00 g). Regarding the first harvest, the highest fresh economic yield per plant occurred with chicken manure (39.25 g), outperforming the lowest goat manure treatment (26.25 g) by 49.52%. Furthermore, a dosage of 5 tons/ha resulted in the maximum fresh economic yield for the third harvest (34.33 g), a 32.90% improvement over the lowest dosage (25.83 g).